Preoperative information received, its importance and anxiety level of patients at surgical wards of Hospital Universiti Sains Malaysia (Hospital USM) - Ghazali, Nurhidayu (Universiti Sains Malaysia, 2013)
Patients undergoing surgery still claimed that they received inadequate preoperative information. Even though, it is a common procedure for many surgical procedures, information needs is often overlooked, this usually lead to anxiety preoperative phase. The goal of this descriptive cross sectional study is to determine the preoperative information received, level of its importance and anxiety level among the surgical patients at Hospital Universiti Sains Malaysia (Hospital USM). This study also examined the association between anxiety level and types of surgery and the difference importance level of preoperative information between male and female. A total of 61 surgical patients who were recruited from surgical wards Hospital USM in this study using purposive sampling. Data were collected from February to March 2013 using self administered Ambulatory Surgical Patients" Perception of Preoperative reaching and Spielberg Trait Anxiety Inventory (STAI) to measure preoperative information received, level of its importance and anxiety level. Data were analyzed using SPSS 20 for frequency, percentage, mean, standard deviation and p-value. Ethical approval was obtained from Research Ethics Community (Human). (USM). Majority preoperative Information received by the surgery patients was at the low level (M-- 5.115. SD= 1.066). Importance level of preoperative information receive by the surgery patients were at moderate level (M-92.37. SD= 10.075). Overall, patients' anxiety level were at moderate level (M=3I.15. SD=12.03). The study found that no significant association between types of surgery and anxiety level (/?=0.343) and also no significant difference of preoperative information importance level between male and female (/?=0.376). Surgical patient received inadequate preoperative information, perceived low level of importance and were having moderate level of anxiety, Thus surgical nurses need to identify individual information needs and institute a structure preoperative teaching guideline and provide information to ensure surgical patient received adequate information before surgery. This will help in eliminating surgery patients’ anxiety preoperatively.